GPT Chat: Useful or Not in Supporting Learning in Higher Education - Ratri Candrasari; Juan Makulua; Yessicka Noviasmy; Korlina Makulua; Siminto Siminto (Yayasan Adra Karima Hubbi, 2024)
Background. Chat GPT is a natural language model developed by OpenAI, based on the GPT (Generative Pretrained Transformer) architecture. It is renowned for its ability to generate text that closely resembles human writing, including in chat and conversational interactions. In the growing digital era, artificial intelligence technology is increasingly playing an important role in various fields, including education. Purpose. This study aims to identify the benefits of using Chat GPT in learning in higher education and how its use can improve the quality of learning, accelerate the assessment process, increase student engagement, improve teaching efficiency, and facilitate student understanding. Method. The research method used is quantitative by using google form which will produce data in the form of numbers. By using google form, a questionnaire will be made and distributed to students in higher education. Results. The results show that the use of Chat GPT has significant benefits in learning in higher education. The use of Chat GPT can improve the quality of learning, accelerate the assessment process, increase student engagement, and improve teaching efficiency. Conclusion. The conclusion from this study is that the use of Chat GPT in a college setting can be beneficial in supporting learning in an innovative and effective way. However, the limitation of this study is that the researcher was only able to conduct a study of a few students in higher education. Therefore, the researcher hopes that future research can be conducted with a wider scope. The researcher also recommends that future research can be a reference material in conducting research related to the utilisation of Chat GPT in supporting learning in higher education.